Preparation method and application of high-stability and high-conductivity composite sodium lignin sulfonate negative electrode
Through the ion cross-linking and high-temperature carbonization treatment of modified sodium lignin sulfonate, a high-stability and conductive composite sodium lignin sulfonate was prepared, which solved the problems of negative plate passivation and charging efficiency of lead-acid batteries at low temperatures, and improved the low-temperature performance and cycle life of the battery.
Patent Information
- Application Number
- CN202510284206.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2025-07-04
AI Technical Summary
The negative electrode plate of lead-acid batteries is prone to passivation and shrinkage under low temperature conditions, resulting in a decline in battery performance. The existing sodium lignin sulfonate additives dissolve in acid circulation, which affects battery performance and charging efficiency.
Through ionic cross-linking and high-temperature carbonization treatment of modified sodium lignin sulfonate, a high-stability and conductive composite sodium lignin sulfonate is prepared for negative electrode additives to ensure that it exists stably in the acid and has conductive ability, reduce the internal resistance of the negative electrode, and improve electrochemical reversibility.
It improves the low-temperature performance, discharge capacity and cycle life of the battery, reduces the charging voltage and temperature, ensures the effective addition of sodium lignin sulfonate, and improves the performance of the battery at different stages.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lead-acid batteries, and particularly relates to a preparation method and application of a high-stability and high-conductivity composite sodium lignin sulfonate negative electrode. Background Art
[0002] As a power battery, lead-acid batteries have many advantages such as low price, easy use, energy saving and environmental protection. In recent years, with the rapid development of electric forklifts and short-distance pure electric vehicles, there are more and more special application scenarios such as cold storage and northern winter, which puts higher requirements on the low-mixing performance of batteries. At the same time, industries such as golf carts, tourist sightseeing vehicles, cleaning vehicles, patrol vehicles and other field electric vehicles are also developing. The requirements for low-temperature capacity have been reduced from -18℃ to -20℃, and the discharge capacity has been increased from 0.5C3 to 0.7C3. Users have higher and higher demands for low temperatures. The low-temperature performance of lead-acid batteries mainly depends on the negative plate. Under low temperature conditions, the main failure mode of the negative plate is passivation and shrinkage to varying degrees. Practice has proved that adding appropriate additives to the negative active material is one of the main solutions. Sodium lignin sulfonate, as one of the most commonly used additives for the negative electrode, has been used in lead-acid batteries for 150 years. It can adsorb lead ions on the surface of the negative electrode, slow down the recrystallization of lead sulfate crystals and inhibit the occurrence of passivation of the negative plate, effectively improving the negative electrode capacity, low-temperature performance and life. However, the current formation method of lead-acid batteries generally adopts an acid circulation formation process. During the battery formation process, a portion of the sodium lignin sulfonate in the negative plate will dissolve into the electrolyte, especially in the early stage of battery formation. Due to the low density of the electrolyte and the high temperature, the dissolution amount of sodium lignin sulfonate is relatively large, and the dissolved sodium lignin sulfonate will be taken away from the battery by the circulating acid, resulting in the loss of the actual amount of sodium lignin sulfonate added, causing the battery performance to decline. At the same time, studies have found that due to its own structure and nearly non-conductive properties, during the charging process, the surface of the negative electrode is covered by sodium lignin sulfonate, resulting in the lead ion reduction reaction being hindered, the electrode polarization is serious, and the charging voltage is increased, resulting in the charging process being hindered, and the degree of sulfation of the electrode surface is aggravated, which in turn affects the battery's cycle performance. Summary of the invention
[0003] The invention provides a preparation method and application of a high-stability and high-conductivity composite sodium lignin sulfonate negative electrode. The composite sodium lignin sulfonate can stably exist in acid and has the ability to conduct electricity and adsorb lead ions, and can effectively alleviate the precipitation of the negative electrode in acid cycle formation, ensure the effective addition amount of sodium lignin sulfonate, reduce the internal resistance of the negative electrode, improve the electrochemical reversibility of the negative electrode, reduce the charging voltage and temperature, and thus improve the low-temperature performance, discharge capacity and cycle life of the battery.
[0004] The technical solution of the present invention is: In a first aspect, a method for preparing a high-stability and high-conductivity composite sodium lignosulfonate negative electrode is disclosed, comprising the following steps: 1) Preparation of high-stability sodium lignosulfonate: Weigh zinc sulfate, add it to water and dissolve it to prepare a zinc-rich aqueous solution; then prepare a mixed aqueous solution of sodium lignosulfonate, carboxymethyl chitosan and polyethylene glycol, and drop the mixed aqueous solution into the zinc-rich solution under stirring. Continue stirring for ionic crosslinking, then add polyethylene polyamine and isopropanol to the system, and continue stirring until the reaction ends. Centrifuge, wash and dry to obtain high-stability sodium lignosulfonate; 2) Preparation of conductive sodium lignosulfonate: Using sodium lignosulfonate as a carbon source, directly carbonize sodium lignosulfonate and combine with the chemical activation of potassium hydroxide to construct three-dimensional porous conductive sodium lignosulfonate; 3) Preparation of negative electrode additive: Mix the high-stability sodium lignosulfonate obtained in step 1), the conductive sodium lignosulfonate obtained in step 2) and unmodified sodium lignosulfonate to form a mixed sodium lignosulfonate; 4) Preparation of negative electrode lead paste: Dry-mix lead powder, mixed sodium lignosulfonate, barium sulfate and short fibers in a paste mixer. After the dry mixing is completed, add water to the mixed powder and stir to form a water-mixed lead paste. Add sulfuric acid to the water-mixed lead paste and mix while stirring to obtain the negative electrode lead paste; 5) Preparation of negative electrode plate: Coat the lead paste on the grid, wrap it with a coating paper after coating, and then cure and dry the negative green plate to obtain the negative electrode plate.
[0005] Preferably, in step 1), the concentration of zinc sulfate in the zinc-rich aqueous solution is 1-4%, the mass ratio of sodium lignosulfonate, carboxymethyl chitosan and polyethylene glycol is 5-12:1-12:1-2, and the ionic crosslinking reaction time is 1-4 h.
[0006] Preferably, in step 1), the mass-to-volume ratio of polyethylene polyamine to isopropanol is (1-8 g):5 mL, the reaction time is 3-8 h; the drying temperature is 60-80 °C and the time is 18-32 h.
[0007] Preferably, in step 2), sodium lignosulfonate is first dried at 40-70 °C for 10-15 h, and sodium lignosulfonate and potassium hydroxide are mixed and ground evenly according to a mass ratio of 1:0.8-1.2 to form a mixture. Then the mixture is placed in a tubular furnace, heated to the carbonization temperature of 650-850 °C under nitrogen protection, kept warm for 2-3 h and then cooled naturally. After the product is cooled, soak it in 1-2 mol / L hydrochloric acid for 10-12 h, then wash it alternately with deionized water and ethanol until neutral, and finally place the product in a vacuum drying oven for drying. The vacuum drying temperature is 60-80 °C and the drying time is 24-36 h to obtain three-dimensional porous conductive sodium lignosulfonate.
[0008] Preferably, in step 3), the mixed sodium lignosulfonate is ground and sieved through a sieve with 800 mesh.
[0009] Preferably, in step 3), the mass ratio of the added highly stable sodium lignosulfonate, conductive sodium lignosulfonate and unmodified sodium lignosulfonate is 1-10:1-10:1-5.
[0010] Preferably, in step 4), the negative electrode lead paste contains the following components in parts by weight: 100 parts of lead powder, 0.05-0.12 parts of short fiber, 0.4-1.4 parts of barium sulfate, 1-4 parts of mixed sodium lignosulfonate, 10.0-12.5 parts of deionized water and 7-12 parts of sulfuric acid, and the density of sulfuric acid is 1.38 g / cm 3 .
[0011] Preferably, in step 5), the curing and drying is to put the negative electrode into a constant temperature and humidity device for curing and drying. The procedure is as follows: first, dry for 48-52 h under the conditions of a temperature of 50-70 °C and a humidity of 85-95%, and then continue to dry for 24-30 h under the conditions of a temperature of 60-80 °C and a relative humidity ≤ 10%.
[0012] In the second aspect, a negative electrode plate prepared by the preparation method described above is disclosed.
[0013] In the third aspect, the application of the negative electrode plate in preparing a negative electrode of a lead-acid battery is disclosed.
[0014] By directionally modifying industrial natural lignin and using the lignosulfonates before and after modification in combination, lignins with different physicochemical structural characteristics play the role of a negative electrode expander at different stages of the battery. First, a free radical initiator is used to initiate ionic cross-linking between sodium lignosulfonates, and then a modified highly stable sodium lignosulfonate is obtained by reacting with polyethylene polyamine and isopropyl alcohol. The modified highly stable sodium lignosulfonate has high acid resistance, can stably exist in sulfuric acid and does not undergo high-temperature dissolution. At the same time, the adsorption capacity of the modified highly stable sodium lignosulfonate for lead ions is greatly improved, which can further alleviate the passivation of the negative electrode at low temperature, improve the low-temperature performance and discharge capacity of the battery. Secondly, the sodium lignosulfonate is carbonized by a high-temperature direct carbonization method, and the obtained modified sodium lignosulfonate has relatively high conductivity and cross-linking degree, and a three-dimensional structure with multi-level stratification formed by micropores and mesopores after cross-linking, which can solve the problem of serious polarization caused by the non-conductivity of lignin itself, reduce the charging voltage and charging temperature, and extend the battery cycle life. Moreover, the conductive sodium lignosulfonate can be randomly arranged and in contact with each other in the lead paste during mixing, reducing the tortuosity factor of the electrode voids, facilitating the diffusion and migration of lead ions and sulfate ions, further reducing the electrode internal resistance, and improving the discharge capacity of the battery.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The mixed sodium lignosulfonate of the present invention includes highly stable sodium lignosulfonate after modification, conductive sodium lignosulfonate after carbonization modification, and unmodified sodium lignosulfonate. The unmodified sodium lignosulfonate will gradually dissolve and disperse on the electrolyte and electrode surface during the formation stage, which can effectively improve the viscosity and conductivity of the electrolyte at low temperature, and improve the initial capacity and low-temperature starting ability of the battery; the characteristic of highly stable sodium lignosulfonate is that it can stably exist in high-density sulfuric acid, and at the same time, the adsorption ability of highly stable sodium lignosulfonate to lead ions is greatly improved, which can delay the passivation phenomenon of the negative electrode during the charge and discharge process of the battery, and improve the discharge capacity and service life of the battery; conductive sodium lignosulfonate can reduce the tortuosity coefficient of the electrode pores, which is beneficial to the diffusion and migration of lead ions and sulfate ions, reduce the internal resistance of the electrode, can further reduce the charging voltage, improve the charging acceptance ability of the battery, and can improve the service life of the battery. By utilizing the dispersibility, acid stability and conductivity of the three, it can not only ensure the stable maintenance of the effective addition amount of the composite lignin in the whole use cycle of the battery, but also play a synergistic role in different stages of battery use to ensure good battery performance. Starting from the technical mechanism, through in-depth research on the polymerization modification, high-temperature carbonization of sodium lignosulfonate and its characteristics in the battery environment, while maintaining better improvement of the charging acceptance performance of the battery, the low-temperature starting performance and high-temperature cycle life are synchronously considered, and the comprehensive performance of the battery is excellent. Detailed implementation manners
[0016] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions will be clearly and completely described below in conjunction with the embodiments of the present invention. All raw materials used in the examples and comparative examples are commercially available unless otherwise specified. Sodium lignosulfonate was purchased from Shanghai Macklin Biochemical Co., Ltd., carboxymethyl chitosan, polyethylene glycol and zinc sulfate were all purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., isopropanol and polyethylene polyamine were purchased from Tianjin Guangfu Technology Development Co., Ltd., and short fibers were purchased from Changzhou Tianyi Engineering Fiber Co., Ltd.
[0017] It should be noted that the parts involved in the preparation process of the negative electrode lead paste in the examples and comparative examples are parts by mass.
[0018] Example 1 This example provides a preparation method for a negative electrode of highly stable and highly conductive composite sodium lignosulfonate, including the following steps: 1) Preparation of high-stability sodium lignin sulfonate: weigh 10g of zinc sulfate, add 1L of deionized water to dissolve, and prepare a zinc-rich aqueous solution with a concentration of 1%; then weigh 12g of sodium lignin sulfonate, 12g of carboxymethyl chitosan and 2g of polyethylene glycol respectively, add them to 200mL of deionized water to obtain a mixed aqueous solution, add the mixed aqueous solution dropwise to the zinc-rich solution under stirring, continue stirring for 4h to cause ionic crosslinking, then add 40g of polyethylene polyamine and 50mL of isopropanol to the system, continue stirring the reaction for 8h until the end, wash with deionized water by centrifugation 3 times, and dry in a 60℃ vacuum drying oven for 32h to obtain high-stability sodium lignin sulfonate; 2) Preparation of conductive sodium lignin sulfonate: Sodium lignin sulfonate is first dried in an oven at 40°C for 15 hours, and then sodium lignin sulfonate and potassium hydroxide are mixed and ground evenly in a mass ratio of 1:1 to form a mixture. The mixture is placed in a tubular furnace and heated to 700°C at 5°C / min under nitrogen protection and kept warm for 2 hours to complete carbonization and activation. After the product is cooled, it is soaked in 1 mol / L hydrochloric acid for 12 hours to remove residual KOH and impurities. Finally, it is washed alternately with deionized water and ethanol until neutral, and vacuum dried at 80°C for 24 hours to obtain three-dimensional porous conductive sodium lignin sulfonate; 3) Preparation of negative electrode additive: The high-stability sodium lignin sulfonate obtained in step 1) and the conductive sodium lignin sulfonate obtained in step 2) are mixed and stirred at a mass ratio of 1:1 for 3 hours, ground and sieved with a mesh size of 800 mesh, and then fully mixed with unmodified sodium lignin sulfonate at a mass ratio of 5:1 to prepare mixed sodium lignin sulfonate; 4) Preparation of negative lead paste: 100 parts of lead powder, 1 part of mixed sodium lignin sulfonate, 0.4 parts of barium sulfate and 0.05 parts of short fiber were dry mixed in a paste mixer for 5 minutes. After the dry mixing was completed, 10 parts of deionized water were added to the mixed powder and stirred for 5 minutes to form a water-mixed lead paste. 7 parts of 1.38 g / cm 3 Add sulfuric acid while stirring, and mix for 30 minutes to obtain the negative electrode lead paste; 5) Preparation of negative plate: Apply 15g of lead paste on the quaternary alloy continuous negative plate grid, evenly coat both sides, and wrap both sides with coated paper to obtain negative plate, then put the negative plate into a constant temperature and humidity drying oven, according to the procedure: first dry for 48 hours at 50℃ and 95% humidity, then continue to dry for 30 hours at 60℃ and ≤10% relative humidity, and obtain the negative plate after curing and drying, and form a three-positive and two-negative battery with the separator and the positive electrode. The separator and positive plate are all mass-produced products. Assemble the battery for standby use, numbered 1#.
[0019] Example 2 This embodiment provides a method for preparing a high-stability and high-conductivity composite sodium lignin sulfonate negative electrode, comprising the following steps: 1) Preparation of high-stability sodium lignin sulfonate: Weigh 40g of zinc sulfate, add 1L of deionized water to dissolve, and prepare a zinc-rich aqueous solution with a concentration of 4%; then weigh 5g of sodium lignin sulfonate, 5g of carboxymethyl chitosan and 1.5g of polyethylene glycol respectively, add them to 200mL of deionized water to obtain a mixed aqueous solution, add the mixed aqueous solution dropwise to the zinc-rich solution under stirring, continue stirring for 1h to cause ionic crosslinking, then add 10g of polyethylene polyamine and 50mL of isopropanol to the system, continue stirring the reaction for 3h until the end, wash with deionized water by centrifugation 3 times, and dry in a vacuum drying oven at 70°C for 24h to obtain high-stability sodium lignin sulfonate; 2) Preparation of conductive sodium lignin sulfonate: Sodium lignin sulfonate is first dried in an oven at 55°C for 12 hours, and then sodium lignin sulfonate and potassium hydroxide are mixed and ground evenly in a mass ratio of 1:0.8 to form a mixture. The mixture is placed in a tubular furnace and heated to 850°C at 5°C / min under nitrogen protection and kept warm for 2 hours to complete carbonization and activation. After the product is cooled, it is soaked in 1 mol / L hydrochloric acid for 12 hours to remove residual KOH and impurities. Finally, it is washed alternately with deionized water and ethanol until neutral, and vacuum dried at 60°C for 36 hours to obtain three-dimensional porous conductive sodium lignin sulfonate; 3) Preparation of negative electrode additive: The high-stability sodium lignin sulfonate obtained in step 1) and the conductive sodium lignin sulfonate obtained in step 2) are mixed and stirred at a mass ratio of 5:1 for 3 hours, ground and sieved with a mesh size of 800 mesh, and then fully mixed with unmodified sodium lignin sulfonate at a mass ratio of 10:3 to prepare mixed sodium lignin sulfonate; 4) Preparation of negative electrode lead paste: 100 parts of lead powder, 4 parts of mixed sodium lignin sulfonate, 1 part of barium sulfate and 0.08 parts of short fiber were dry mixed in a paste mixer for 5 minutes. After the dry mixing was completed, 12.5 parts of deionized water were added to the mixed powder and stirred for 5 minutes to form a water-mixed lead paste. 9 parts of 1.38 g / cm 3 Add sulfuric acid while stirring, and mix for 30 minutes to obtain the negative electrode lead paste; 5) Preparation of negative plate: Apply 15g of lead paste on the quaternary alloy continuous negative plate grid, evenly coat both sides, and wrap both sides with coated paper to obtain negative plate, then put the negative plate into a constant temperature and humidity drying oven, and follow the procedure: first dry for 50h at 60℃ and 90% humidity, then continue drying for 27h at 70℃ and ≤10% relative humidity, and obtain the negative plate after curing and drying, and form a three-positive and two-negative battery with the separator and the positive electrode. The separator and positive plate are all mass-produced products. Assemble the battery for standby use, numbered 2#.
[0020] Example 3 This embodiment provides a method for preparing a high-stability and high-conductivity composite sodium lignin sulfonate negative electrode, comprising the following steps: 1) Preparation of sodium lignosulfonate with high stability: Weigh 2 g of zinc sulfate, add it to 1 L of deionized water and dissolve it to prepare a zinc-rich aqueous solution with a concentration of 2%. Then, weigh 6 g of sodium lignosulfonate, 12 g of carboxymethyl chitosan and 1 g of polyethylene glycol respectively, add them to 200 mL of deionized water to obtain a mixed aqueous solution. Under stirring, the mixed aqueous solution is dropped into the zinc-rich solution, and stirring is continued for 2 h to occur ionic crosslinking. Then, add 80 g of polyethylene polyamine and 50 mL of isopropanol to the system, and continue stirring and reacting for 5 h until the end. After centrifuging and washing with deionized water 3 times, it is placed in a vacuum drying oven at 80 °C and dried for 18 h to obtain sodium lignosulfonate with high stability; 2) Preparation of conductive sodium lignosulfonate: After sodium lignosulfonate is dried in an oven at 70 °C for 10 h, sodium lignosulfonate and potassium hydroxide are mixed and ground evenly according to a mass ratio of 1:1.2 to form a mixture. The mixture is placed in a tube furnace, and under nitrogen protection, it is heated to 650 °C at a rate of 5 °C / min and kept warm for 2 h to complete carbonization and activation. After the product is cooled, it is soaked in 1 mol / L hydrochloric acid for 12 h to remove residual KOH and impurities. Finally, it is washed alternately with deionized water and ethanol until neutral, and dried in a vacuum at 70 °C for 30 h to obtain three-dimensional porous conductive sodium lignosulfonate; 3) Preparation of the negative electrode additive: The sodium lignosulfonate with high stability obtained in step 1) and the conductive sodium lignosulfonate obtained in step 2) are mixed and stirred for 3 h according to a mass ratio of 1:1, ground and then sieved through a sieve with a mesh number of 800 meshes, and then fully mixed with unmodified sodium lignosulfonate according to a mass ratio of 1:1 to prepare a mixed sodium lignosulfonate; 4) Preparation of the negative electrode lead paste: 100 parts of lead powder, 3 parts of the mixed sodium lignosulfonate, 1.4 parts of barium sulfate and 0.12 part of short fiber are dry-mixed in a paste mixer for 5 min. After the dry mixing is completed, 11 parts of deionized water are added to the mixed powder, and stirred for 5 min to form a water-mixed lead paste. 12 parts of sulfuric acid with a density of 1.38 g / cm 3 is added to the water-mixed lead paste while stirring, and mixed for 30 min to obtain the negative electrode lead paste; 5) Preparation of the negative electrode plate: 15 g of lead paste is coated on the negative electrode grid of the quaternary alloy continuous punching, and after being evenly coated on both sides, it is wrapped with coating paper on both sides to obtain a negative green plate. Then, the negative green plate is placed in a constant temperature and humidity drying oven. According to the procedure: first, it is dried at a temperature of 70 °C and a humidity of 85% for 52 h, and then at a temperature of 80 °C and a relative humidity ≤ 10% for 24 h. After curing and drying, the negative electrode plate is obtained, which is combined with a separator and a positive electrode to form a three-positive and two-negative battery. The separator and the positive electrode plate are both products of mass production. Assemble the battery for standby and number it as 3#.
[0021] Example 4 This example provides a preparation method of a negative electrode of high-stability and high-conductivity composite sodium lignosulfonate, including the following steps: 1) Preparation of highly stable sodium lignosulfonate: Weigh 40 g of zinc sulfate, add it to 1 L of deionized water and dissolve it to prepare a zinc-rich aqueous solution with a concentration of 4%. Then weigh 7 g of sodium lignosulfonate, 5 g of carboxymethyl chitosan and 1 g of polyethylene glycol respectively and add them to 200 mL of deionized water to obtain a mixed aqueous solution. Under stirring, the mixed aqueous solution is dropped into the zinc-rich solution, and ion crosslinking occurs after continuous stirring for 4 h. Then add 80 g of polyethylene polyamine and 50 mL of isopropanol to the system, and continue stirring and reacting for 5 h until the end. After centrifuging and washing with deionized water 3 times, it is placed in a vacuum drying oven at 70 °C and dried for 24 h to obtain highly stable sodium lignosulfonate; 2) Preparation of conductive sodium lignosulfonate: After sodium lignosulfonate is dried in an oven at 50 °C for 10 h, sodium lignosulfonate and potassium hydroxide are mixed and ground evenly according to a mass ratio of 1:1 to form a mixture. The mixture is placed in a tubular furnace, and under nitrogen protection, it is heated to 850 °C at a rate of 3 °C / min and kept warm for 2 h to complete carbonization and activation. After the product is cooled, it is soaked in 1 mol / L hydrochloric acid for 12 h to remove residual KOH and impurities. Finally, it is washed alternately with deionized water and ethanol until neutral, and dried in a vacuum at 80 °C for 24 h to obtain three-dimensional porous conductive sodium lignosulfonate; 3) Preparation of negative electrode additive: The highly stable sodium lignosulfonate obtained in step 1) and the conductive sodium lignosulfonate obtained in step 2) are mixed and stirred for 3 h according to a mass ratio of 5:8, ground and then sieved through a sieve with a mesh size of 800 mesh, and then fully mixed with unmodified sodium lignosulfonate according to a mass ratio of 3:1 to prepare a mixed sodium lignosulfonate; 4) Preparation of negative electrode lead paste: 100 parts of lead powder, 4 parts of mixed sodium lignosulfonate, 0.4 part of barium sulfate and 0.07 part of short fiber are dry-mixed in a paste mixer for 5 min. After dry-mixing is completed, 12.5 parts of deionized water are added to the mixed powder, and stirred for 5 min to form a water-mixed lead paste. 7 parts of sulfuric acid with a density of 1.38 g / cm 3 is added to the water-mixed lead paste while stirring, and mixed for 30 min to prepare the negative electrode lead paste; 5) Preparation of negative electrode plate: 15 g of lead paste is coated on a four-element alloy continuous punching negative electrode grid. After both sides are evenly coated, it is wrapped with two pieces of coating paper to obtain a negative green plate. Then the negative green plate is placed in a constant temperature and humidity drying oven. According to the procedure: first, it is dried at a temperature of 70 °C and a humidity of 95% for 48 h, and then at a temperature of 60 °C and a relative humidity ≤ 10% for 30 h. After curing and drying, a negative electrode plate is obtained, which is combined with a separator and a positive electrode to form a three-positive and two-negative battery. The separator and the positive electrode plate are both mass-produced products. Assemble the battery for standby and number it as 4#.
[0022] Comparative Example 1 Different from Example 1, this comparative example does not include Step 2), and Step 3) is as follows: Preparation of the negative electrode additive: Grind the highly stable sodium lignosulfonate obtained in Step 1), sieve it through a sieve with 800 mesh, and then fully mix it with unmodified sodium lignosulfonate in a mass ratio of 5:1 to form a mixed sodium lignosulfonate; the remaining preparation methods and steps are the same as those in Example 1. Assemble the battery for standby, numbered 5#.
[0023] Comparative Example 2 Different from Example 1, this comparative example does not include Step 1), and Step 3) is as follows: Preparation of the negative electrode additive: Grind the obtained conductive sodium lignosulfonate, sieve it through a sieve with 800 mesh, and then fully mix it with unmodified sodium lignosulfonate in a mass ratio of 5:1 to form a mixed sodium lignosulfonate; the remaining preparation methods and steps are the same as those in Example 1. Assemble the battery for standby, numbered 6#.
[0024] Comparative Example 3 Preparation of the sodium lignosulfonate negative electrode plate is specifically as follows: 1) Preparation of the negative electrode lead paste: Dry mix 100 parts of lead powder, 1 part of sodium lignosulfonate, 0.4 part of barium sulfate, 0.05 part of short fiber, and 0.1 part of acetylene black in a paste mixer for 5 min. After the dry mixing is completed, add 10 parts of deionized water to the mixed powder and stir for 5 min to form a water-mixed lead paste. Add 7 parts of sulfuric acid with a density of 1.38 g / cm 3 while stirring, and mix for 30 min to obtain the negative electrode lead paste; 2) Preparation of the negative electrode plate: Coat 15 g of the lead paste on the four-element alloy continuous punching negative electrode grid. After evenly coating both sides, wrap it with coating paper on both sides to obtain a negative green plate. Then, place the negative green plate in a constant temperature and humidity drying oven. According to the procedure: First, dry it at a temperature of 50°C and a humidity of 95% for 48 h, and then continue to dry it at a temperature of 60°C and a relative humidity of ≤10% for 30 h. After curing and drying, obtain the negative electrode plate, which forms a three-positive and two-negative battery with the separator and the positive electrode. The separator and the positive electrode plate are both mass-produced products. Assemble the battery for standby, numbered 7#.
[0025] Comparative Example 4 Different from Example 1, in Step 3), it is not sieved through a sieve after grinding. The remaining preparation methods and steps are the same as those in Example 1. Assemble the battery for standby, numbered 8#.
[0026] Comparative Example 5 Different from Example 2, in Step 1), the addition amount of zinc sulfate is 45 g, which is dissolved in 1 L of deionized water to prepare a zinc-rich aqueous solution with a concentration of 4.5%. The remaining preparation methods and steps are the same as those in Example 2. Assemble the battery for standby, numbered 9#.
[0027] Comparative Example 6 Different from Example 1, the addition amount of polyethylene polyamine in step 1) is 45 g, and the remaining preparation methods and steps are the same as those in Example 2. Assemble the battery for standby and number it 10#.
[0028] Comparative Example 7 Different from Example 1, step 3) is the preparation of the negative electrode additive: Mix the highly stable sodium lignosulfonate obtained in step 1) and the conductive sodium lignosulfonate obtained in step 2) at a mass ratio of 1:1, stir for 3 h, grind and then sieve through a sieve with a mesh number of 800 to prepare a mixed sodium lignosulfonate; the remaining preparation methods and steps are the same as those in Example 1. Assemble the battery for standby and number it 11#.
[0029] Refer to the standard QCT 742—2009 "Lead-acid Batteries for Electric Vehicles": At -20°C, the C3 capacity is not less than 55% of the rated capacity. Conduct low-temperature capacity tests on the batteries numbered 1# - 11# prepared in the above examples and comparative examples. The test procedure is as follows: (1) The fully charged battery is left stationary in a low-temperature chamber at -20°C ± 2°C for 20 h; (2) Discharge at a constant current of I3 until 1.40 V, record the discharge time t (-20°C), and calculate the discharge capacity.
[0030] Table 1 Low-temperature Capacity Test of Batteries
[0031] As can be seen from Table 1, the low-temperature capacity tests of Batteries 1-11# are all qualified, indicating that the assembled batteries are in good condition and can be charged and discharged normally. The low-temperature capacity of the batteries in Embodiment Cases 1-4# is about 140% more than the standard requirement, indicating that the mixed lignin plays a significant role. Among them, the low-temperature performance of the mixed lignin prepared in Example 1 is the best. From the batteries 5# and 6# prepared in Comparative Examples 1 and 2, it can be seen that when the highly stable sodium lignosulfonate and the highly conductive sodium lignosulfonate are separately mixed with sodium lignosulfonate, the effect is not as good as when the three are mixed. The main reason is that although the highly stable sodium lignosulfonate can stably exist in sulfuric acid and does not undergo high-temperature dissolution, the negative electrode does not have an additional conductive agent, resulting in an increase in the charging voltage and serious battery heating. Therefore, the performance of Battery 5# is worse than that of Battery 1#. Although the conductive sodium lignosulfonate has relatively high conductivity and cross-linking degree and can solve the problem of serious polarization caused by the non-conductivity of lignin itself, its ability to adsorb lead ions on the surface of the negative electrode is low. Thus, it cannot effectively slow down the recrystallization of lead sulfate crystals and inhibit the passivation of the negative electrode plate during the chemical reaction process, resulting in the performance of Battery 6# being inferior to that of Battery 1#. The low-temperature C3 capacity of Battery 7# prepared in Comparative Example 3 is significantly reduced, mainly because most of the sodium lignosulfonate added to the negative electrode flows out of the battery during the formation process, resulting in the actual content of sodium lignosulfonate being much lower than the added amount. In Comparative Examples 5 and 6, the mass concentration of zinc sulfate and the content of polyvinylamine are increased respectively, and the battery capacity is reduced. The main reason is that the introduction of excessive zinc sulfate and amine is equivalent to impurities in the battery cycle. The introduction of impurities will cause self-discharge of the battery, thereby affecting the battery capacity.
[0032] The cycle performance tests were carried out on the batteries prepared in Example 1, Comparative Example 3, and Comparative Example 7. On the basis of referring to the standard GB / T5008.1-2013 "Lead-acid starter batteries - Part 1: Technical conditions and test methods", the test method for cycle durability I performance was adjusted to a certain extent: under the condition of 25°C ± 2°C, discharge at a constant current of I4 for 1 h; charge at a constant voltage with current limiting for 2.5 h, and then continue to charge with a small current of I8 for 0.5 h. One charge and discharge cycle is a cycle unit, and the number of cycle units is recorded.
[0033] Table 2 Cycle Performance Determination
[0034] As can be seen from Table 2, the cycle durability of Comparative Example 3 was unqualified. After dissection, it was found that the positive plate was basically normal, but the negative lead paste shrank severely, causing most of the lead paste to separate from the grid. As a result, the failure of the battery was caused by the shrinkage of the negative active material. The reason was that as the charge-discharge cycle proceeded, sodium lignosulfonate in the negative electrode gradually dissolved into the electrolyte, ultimately leading to the shrinkage of the negative plate lead paste. By comparing Example 1 and Comparative Example 7, it can be seen that the performance of the negative electrode without adding unmodified sodium lignosulfonate was slightly worse. The reason was that there was no soluble sodium lignosulfonate in Comparative Example 7, so the physical and chemical properties of the electrolyte could not be improved, which would affect the ionic conductivity of the electrolyte, and thus the internal resistance of the battery was larger than that of Example 1, ultimately resulting in slightly worse cycle performance. By comparing Example 1 with Comparative Examples 3 and 7, it can be found that the effect of mixing three kinds of sodium lignosulfonates as additives was the best. Using unmodified sodium lignosulfonate alone, the battery cycle performance was unqualified. Using only modified sodium lignosulfonate alone, its cycle durability was qualified, but it was 105 times less than that of Example 1.
[0035] Referring to the national standard GB / T 43346-2023 "Technical Conditions for Starting and Stopping Lead-Acid Batteries", the 1#-11# batteries prepared above were subjected to a -18°C low-temperature starting ability test. The test procedure was as follows: (1) The fully charged battery was placed in a low-temperature box at -18°C ± 1°C and left stationary for 24 h; (2) Discharge at a current of I cc A for 30 s within 2 min, and record the battery terminal voltage at 10 s and 30 s of discharge. The results are shown in Table 3.
[0036] Table 3 Battery Low-Temperature Charging Acceptance Ability Test
[0037] As can be seen from Table 3, except for Comparative Example 4, the -18°C starting performance of other batteries met the standard requirements. The voltage of the batteries in Examples 1-4 was higher than that of Comparative Examples 1-3, indicating that the low-temperature starting ability of the batteries in the examples was better than that of the comparative examples. Furthermore, it shows that sodium lignosulfonate mixed in any ratio can improve the low-temperature starting performance of the battery. By comparing Comparative Examples 1 and 2, it can be seen that conductive sodium lignosulfonate was not as effective in improving low-temperature starting performance as stable sodium lignosulfonate, but both were better than the batteries in Comparative Example 3, indicating that modification had a certain positive effect. In Comparative Examples 5 and 6, the introduction of excessive zinc sulfate and amine was equivalent to impurities for the battery cycle. The impurities would cause the battery water loss to increase, resulting in an increase in the electrolyte density and viscosity, ultimately affecting its low-temperature starting performance. The low-temperature starting performance of Comparative Example 4 was unqualified. The reason was that the un-screened mixed sodium lignosulfonate had different molecular weight distributions, resulting in uneven dispersion in the lead paste, causing lead paste shrinkage and aggregation, accelerating the detachment of the plate, and thus resulting in unqualified low-temperature performance.
[0038] Although the present invention has been described in detail by way of preferred embodiments, the present invention is not limited thereto. Without departing from the spirit and essence of the present invention, those of ordinary skill in the art can make various equivalent modifications or substitutions to the embodiments of the present invention, and these modifications or substitutions should all fall within the scope covered by the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.
Claims
1. Preparation method of composite lignosulfonate negative electrode with high stability and high conductivity, characterized in that, It includes the following steps: 1) Preparation of highly stable sodium lignosulfonate: Weigh zinc sulfate, dissolve it in water to prepare a zinc-rich aqueous solution; then prepare a mixed aqueous solution of sodium lignosulfonate, carboxymethyl chitosan, and polyethylene glycol, and drop the mixed aqueous solution into the zinc-rich solution under stirring. Continue stirring for ionic crosslinking, then add polyethylene polyamine and isopropanol to the system, continue stirring until the reaction ends, and centrifuge, wash, and dry to obtain highly stable sodium lignosulfonate; 2) Preparation of conductive sodium lignosulfonate: Using sodium lignosulfonate as a carbon source, constructing three-dimensional porous conductive sodium lignosulfonate through direct carbonization of sodium lignosulfonate combined with the chemical activation of potassium hydroxide; 3) Preparation of the negative electrode additive: Mix the highly stable sodium lignosulfonate obtained in step 1), the conductive sodium lignosulfonate obtained in step 2), and unmodified sodium lignosulfonate to form a mixed sodium lignosulfonate; 4) Preparation of the negative electrode lead paste: Dry-mix lead powder, mixed sodium lignosulfonate, barium sulfate, and short fibers in a paste mixer. After dry-mixing is completed, add water to the mixed powder and stir to form a water-mixed lead paste. Add sulfuric acid to the water-mixed lead paste and mix while stirring to obtain the negative electrode lead paste; 5) Preparation of the negative electrode plate: Coat the lead paste on the grid, wrap it with a coating paper after coating, and then cure and dry the negative green plate to obtain the negative electrode plate.
2. The preparation method of the high-stability and high-conductivity composite sodium lignosulfonate negative electrode according to claim 1, characterized in that, In step 1), the concentration of zinc sulfate in the zinc-rich aqueous solution is 1-4%, and the mass ratio of sodium lignosulfonate, carboxymethyl chitosan, and polyethylene glycol is 5-12:1-12:1-2, and the ionic crosslinking reaction time is 1-4 h.
3. The preparation method of the high-stability and high-conductivity composite lignosulfonate negative electrode according to claim 1, characterized in that, In step 1), the mass-volume ratio of polyethylene polyamine to isopropanol is (1-8 g):5 mL, the reaction time is 3-8 h; the drying temperature is 60-80 °C, and the time is 18-32 h.
4. The preparation method of the high-stability and high-conductivity composite lignosulfonate negative electrode according to claim 1, characterized in that, In step 2), sodium lignosulfonate is first dried at 40-70 °C for 10-15 h, and sodium lignosulfonate and potassium hydroxide are mixed and ground evenly according to a mass ratio of 1:0.8-1.2 to form a mixture; then the mixture is placed in a tube furnace, heated to the carbonization temperature of 650-850 °C under nitrogen protection, kept warm for 2-3 h, and then cooled naturally; after the product is cooled, it is soaked in 1-2 mol / L hydrochloric acid for 10-12 h, washed alternately with deionized water and ethanol until neutral, and finally the product is placed in a vacuum drying oven for drying. The vacuum drying temperature is 60-80 °C, and the drying time is 24-36 h to obtain three-dimensional porous conductive sodium lignosulfonate.
5. The preparation method of the high-stability and high-conductivity composite lignosulfonate negative electrode according to claim 1, characterized in that, In step 3), the mixed sodium lignosulfonate is ground and sieved, and the mesh number of the sieve is 800 mesh.
6. The preparation method of the high-stability and high-conductivity composite lignosulfonate negative electrode according to claim 1, characterized in that, In step 3), the mass ratio of the added highly stable sodium lignosulfonate, conductive sodium lignosulfonate, and unmodified sodium lignosulfonate is 1-10:1-10:1-5.
7. The preparation method of the high-stability and high-conductivity composite lignosulfonate negative electrode according to claim 1, characterized in that: In step 4), the negative electrode lead paste contains the following components in parts by weight: 100 parts of lead powder, 0.05-0.12 parts of short fibers, 0.4-1.4 parts of barium sulfate, 1-4 parts of mixed sodium lignosulfonate, 10.0-12.5 parts of deionized water, and 7-12 parts of sulfuric acid.
8. The preparation method of the high-stability and high-conductivity composite lignosulfonate negative electrode according to claim 1, characterized in that: In step 5), the solidification and drying process for the negative electrode is to place it in a constant temperature and humidity device for solidification and drying. The procedure is as follows: First, dry it for 48 - 52 h under the conditions of a temperature of 50 - 70 °C and a humidity of 85 - 95%, and then continue to dry it for 24 - 30 h under the conditions of a temperature of 60 - 80 °C and a relative humidity ≤ 10%.
9. A negative electrode plate prepared by the preparation method according to any one of claims 1 - 8.
10. Use of a negative electrode plate according to claim 9 in the preparation of a negative electrode of a lead-acid battery.